2017
DOI: 10.17221/692/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter wheat season tillage on soil properties and yield of summer maize

Abstract: The North China Plain (NCP) serves as China’s second most important maize production region. Rotary tillage, a popular method used in winter wheat/summer maize systems in the region, has adverse effects on maize production. The current study was conducted to determine whether rotary tillage after subsoiling in the winter wheat season (RS) improves the grain-filling rate and yield of summer maize by decreasing soil bulk density, when compared with rotary tillage (R), in the NCP. The RS treatment decreased soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Agricultural input and output equivalents needed for energy and environmental assessment calculations were used from the literature [8][9][10][11][12][13][14][15][16][17][18][19]. All equivalent values are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Agricultural input and output equivalents needed for energy and environmental assessment calculations were used from the literature [8][9][10][11][12][13][14][15][16][17][18][19]. All equivalent values are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that rotation tillage in the winter wheat season was an important practice that enriched the microbial community structure and increased the soil enzyme activity, thus facilitating the conversion and accumulation of soil nutrients and improving crop yields [ 2 , 5 ]. Deep tillage to 30 cm increased total soil N content in the 0–40 cm soil layer and improved crop root distribution [ 6 ], further promoting crop water efficiency and grain production [ 7 ].…”
Section: Introductionmentioning
confidence: 99%